2022
DOI: 10.1101/2022.11.25.517820
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Instantly adhesive and ultra-elastic patches for dynamic organ and wound repair

Abstract: Bioadhesive materials and patches are promising alternatives to surgical sutures and staples. However, many existing bioadhesives do not meet the functional requirements of current surgical procedures and interventions. Here we present a translational patch material that exhibits: (1) instant adhesion to wet tissues (2.5-fold stronger than Tisseel, an FDA-approved fibrin glue), (2) ultra-stretchability (stretching to >300% its original length without losing elasticity), (3) compatibility with rapid photo-pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 87 publications
1
3
0
Order By: Relevance
“…To confirm the presence of yeast added to our patches, we loaded GFP-expressing yeast into the bioink and printed patches with three different complex geometries mimicking the mechanical, auxetic properties of human skin. 21,32,33 Yeast were visualized in the printed patches by fluorescence microscopy, and as expected fluorescence intensity was higher in yeast-containing patches than control patches without yeast (Fig. 1), demonstrating successful encapsulation of yeast into hydrogels.…”
Section: Patch Design and Optimizationsupporting
confidence: 69%
See 1 more Smart Citation
“…To confirm the presence of yeast added to our patches, we loaded GFP-expressing yeast into the bioink and printed patches with three different complex geometries mimicking the mechanical, auxetic properties of human skin. 21,32,33 Yeast were visualized in the printed patches by fluorescence microscopy, and as expected fluorescence intensity was higher in yeast-containing patches than control patches without yeast (Fig. 1), demonstrating successful encapsulation of yeast into hydrogels.…”
Section: Patch Design and Optimizationsupporting
confidence: 69%
“…For example, we have recently shown that the addition of acrylic acid and calcium can substantially increase tissue adhesion. 32 Future studies will optimize patch composition for tissue adhesion while maintaining yeast viability.…”
Section: Biomaterials Science Papermentioning
confidence: 99%
“…Beyond skin wound repair, patches can be manufactured to help repair the regeneration of lung tissue in cases of puncture wounds and serve as another viable option for potential therapeutic treatment in regenerative medicine. 82 …”
Section: Main Textmentioning
confidence: 99%
“…Another reason could be that the hydrogel-based design elements within the meshes tended to stick to each other when the experiments were performed in air (Figure 2F), which may have prevented them from opening-up when the meshes were stretched. In future, we could perform the stretching of the meshes under water or use a balloon model to further characterize the auxetic characteristics of the meshes, [4,27] to validate the computational models.…”
Section: Algorithmically Defined Computational Models For Rapidly Scr...mentioning
confidence: 99%